Assessment and documentation of non-healing, chronic wounds in inpatient health care facilities in the Czech Republic: an evaluation study - Pokorná, Andrea; Leaper, David (International wound journal, 2015)
The foundation of health care management of patients with non-healing, chronic wounds needs accurate evaluation followed by the selection of an appropriate therapeutic strategy. Assessment of non-healing, chronic wounds in clinical practice in the Czech Republic is not standardised. The aim of this study was to analyse the methods being used to assess non-healing, chronic wounds in inpatient facilities in the Czech Republic. The research was carried out at 77 inpatient medical facilities (8 university/faculty hospitals, 63 hospitals and 6 long- term hospitals) across all regions of the Czech Republic. A mixed model was used for the research (participatory observation including creation of field notes and content analysis of documents for documentation and analysis of qualitative and quantitative data). The results of this research have corroborated the suspicion of inconsistencies in procedures used by general nurses for assessment of non-healing, chronic wounds. However, the situation was found to be more positive with regard to evaluation of basic/fundamental parameters of a wound (e.g. size, depth and location of a wound) compared with the evaluation of more specific parameters (e.g. exudate or signs of infection). This included not only the number of observed variables, but also the action taken. Both were significantly improved when a consultant for wound healing was present (P = 0·047). The same applied to facilities possessing a certificate of quality issued by the Czech Wound Management Association (P = 0·010). In conclusion, an effective strategy for wound management depends on the method and scope of the assessment of non-healing, chronic wounds in place in clinical practice in observed facilities; improvement may be expected following the general introduction of a 'non-healing, chronic wound assessment' algorithm.
Keywords: klinické protokoly; Wound Healing; Nursing practice; rány a poranění; chorobopisy; Medical Records; Chronic wounds; Nurse's Role; lidé; Chronic Disease; Česká republika; Skin Ulcer; chronická nemoc; formuláře a záznamy - kontrola a vedení; Wound management; Czech Republic; hojení ran; Wound assessment; kožní vředy; role ošetřovatelky; Humans; Clinical guidelines; nemocnice; Wounds and Injuries; Forms and Records Control; Hospitals; Clinical Protocols